Green buzz in luxury: Understanding the drivers behind sustainable luxury consumption - Lemponen, Mari (My University, 2020)
Considering the vigorous and consistent growth of the luxury sector, the rise of green consumerism, and modern challenges set by the democratization of luxury, the phenomenon of sustainable luxury has become an area of burgeoning research interest amid academics over recent years. However, based on prior research, we know very little about what consumers understand to be sustainable luxury and what drives them to consume it. To address this research gap, the purpose of this study was set to understand why consumers increasingly consume sustainable luxury. In this study, sustainable luxury refers to a luxury brand that is engaged in socially and/or environmentally sustainable product manufacturing and scope of design. An authentic sustainable luxury brand continuously aims to reduce its negative impact on the environment while ensuring the protection of human rights. To understand consumers’ motivational drivers behind the consumption of sustainable luxury, a qualitative research approach was selected. The data was collected with an application of the ZMET method by conducting six one-on-one in-depth interviews with Finnish consumers. These interviews aimed at uncovering the meanings that consumers attach to sustainable luxury. Arguably an identification and analysis of these meanings helps to understand the motivational drivers that underlie consumers’ growing interest in consumption of sustainable luxury. This study provides preliminary understanding as to the motivational drivers behind sustainable luxury consumption and categorizes them under product-related, personal and social drivers. In terms of managerial implications, the study demonstrates that sustainability can serve as an effective tool for luxury brands to meet the changing needs of consumers and combat the challenges set by the democratization of luxury.

Kestävä kehitys on noussut keskeiseksi kuluttajamarkkinoinnin teema-alueeksi viime vuosien aikana. Yksi keskustelua herättäneistä teemoista on kestävän luksuksen kulutus. Luksussektoria luonnehtivat modernit ilmiöt, kuten toimialan jatkuva kasvu, vastuullisen kuluttajakäyttäytymisen yleistyminen ja luksuksen demokratisoituminen ovat tehneet kestävästä luksuksesta ajankohtaisen aiheen markkinointitieteen saralla. Ajankohtaisuudestaan huolimatta kestävästä luksuksesta löytyy melko niukasti tutkittua tietoa. Tämän tutkielman tarkoituksena oli ymmärtää, miksi kuluttajat kuluttavat kestävää luksusta kasvavassa määrin. Tutkielmassa käsite kestävä luksus viittaa muodin luksusbrändeihin, jotka ovat keskittyneet sosiaalisesti ja/tai ympäristöllisesti vastuulliseen tuotantoon tai tuotedesigniin. Autenttinen kestävä luksusbrändi pyrkii toimenpiteillään vähentämään brändin toiminnasta aiheutuvia ympäristöä rasittavia vaikutuksia ja turvaamaan ihmisoikeuksien toteutumisen. Tutkimus toteutettiin laadullisesti soveltaen ZMET-metodia. Tutkimuksen data kerättiin toteuttamalla kuusi yksilöllistä syvähaastattelua suomalaiselle kohderyhmälle. Haastattelujen avulla pyrittiin löytämään ne merkitykset, joita kuluttajat liittävät kestävään luksukseen. Näiden merkitysten tunnistaminen ja analysointi auttaa ymmärtämään kestävään luksukseen kohdistuvaa kuluttajien kasvavaa mielenkiintoa ja kulutuksen taustalla vaikuttavia motivaatioita. Tutkimuksen tulokset auttavat syventämään kestävän luksuksen kulutukseen liittyvää ymmärrystä. Kestävän luksuksen kulutuksen motivaatiot voidaan kategorisoida tulosten perusteella tuoteperusteisiin, henkilökohtaisiin ja sosiaalisiin ajureihin. Liikkeenjohdollisena suosituksena tutkimus osoittaa kestävyyden olevan luksusbrändeille tehokas keino vastata kuluttajien muuttuviin tarpeisiin ja luksuksen demokratisoitumisen asettamiin haasteisiin.
Keywords: sustainable luxury, democratization of luxury, meanings, motivations, ZMET